Social integration of Afghan migrant women living in Zeytinburnu - Habibullah, Farangis (My University, 2021)
ÖZETZEYTİNBURNUN’DA YAŞAYAN AFGAN KADIN GÖÇMENLERİN TOPLUMSAL ENTEGRASYONUBu çalışma, Türkiye'de Afgan kadınlarının toplumsal entegrasyonunu etkileyen faktörlerin neler olduğunu açıklamayı hedeflemektedir. Afgan kadınlarının Afganistan'dan Türkiye'ye göçünü, göç sonrası toplumsal entegrasyonlarına odaklanarak anlatıyor. Amacım, feminist yaklaşımla, özellikle İstanbul'un Zeytinburnu ilçesinde yaşayan Afgan kadınlarının Türkiye'deki toplumsal entegrasyon “deneyimlerini” not ederek, yerleşimlerini değerlendirmektir. Feminist bakış açısı, kadınların evlilik sonrası rollerindeki değişimler, aile karar alma süreci, işbölümleri ve göç sonrası kadınların öncelikli sorunları gibi göç sürecinde toplumsal cinsiyet ilişkilerinde meydana gelen değişiklikleri açıklar. Feminist bakış açısına göre mülakatlar ve saha çalışması göçmen kadınların entegrasyonunu anlamada en etkili yöntemlerdir. Bu amaçla, çalışma Zeytinburnu'nda 37 Afgan kadınlarla yapılan yüz yüze ve telefon görüşmelerin sonuç ve gözlemlerini içermektedir.Araştırmam sonucunda katılımcıların çoğu benzer ihtiyaçları açıklasa da, bazı deneyimler yine de toplumsal entegrasyonlarındaki mevcut engelleri dile getirdi. Görüşmemden toplanan ve analiz edilen verilere göre görünen odur ki, Afgan kadınlarının yerel düzeyde toplumsal entegrasyonu ile ilgili uygun destek sistemleri yeterli olmadığı için, Afgan kadınları Türkiye'de başarılı bir entegrasyon sağlamak için en fazla sorumluluğu kendileri almak zorundadır. Feminist bakış açısı, savunmasız kadınların güvenli bir toplumsal çevreye ve çalışma ortamlarına ihtiyaç duyduğunu vurgular (Tittensor & Mansouri, 2017). Buradaki temel zorluk, kabul eden ülkelerin kalıcı olarak kalmak isteyen göçmen kadınlar için bir refah planı ve politikaları oluşturamamasıdır. Bu çalışma, Türkiye'de yaşayan Afgan kadınların toplumsal ve ekonomik durumlarının dile getirilmesinin önemini vurgulamaktadır. Afgan kadınlarının toplumsal entegrasyonu konusunda bilincin artırılması için daha çok sayıda kapsamlı araştırmalara ihtiyaç olduğu tespit edilmiştir.

5ABSTRACTSOCIAL INTEGRATION OF AFGHAN MIGRANT WOMEN LIVING IN ZEYTINBURNUThis study aims to explain the factors affecting the social integration of Afghan women in Turkey. It describes the Afghan women's migration from Afghanistan to Turkey, focusing on their social integration after migration. The feminist point of view explains the changes in gender relations during the migration process, such as changes in women's roles after marriage, family decision-making process, labor divisions, and women's prior issues after migration. According to the feminist point of view, interviews and fieldwork are the most effective methods for understanding the integration of migrant women. My goal is to assess the settlement of Afghan women noting the social integration experiences in Turkey, particularly those living in the Zeytinburnu district of Istanbul. It contains the results and observations of the face-to-face interviews and telephone interviews conducted with 37 Afghan women in Zeytinburnu. Although most of the participants explained similar needs, some of the experiences still expressed the existing barriers in their social integration. According to the collected and analyzed data from my interview, Afghan women have to take the most responsibility for successful social integration in Turkey. Since there are no appropriate supporting systems relevant to the Afghan women's social integration at the local and state level. The feminist point of view implies that vulnerable women need the most secure social and labor environments. The challenge here is that receiving countries do not establish a well-being plan and policies for migrant women who want to stay permanently (Tittensor & Mansouri, 2017). This study emphasizes the importance of uttering the social and economic conditions of Afghan women living in Turkey. There is a need for comprehensive researches regarding Afghan women's social integration to enhance consciousness.TABLE OF CONTENTSAbstract………………………………………………………………………………………………………………………………..4Acknowledgment………………………………………………………………………………………………………………..5Table of Contents………………………………………………………………………………………………………………….6Chapter 1INTRODUCTIONIntroduction………………………………………………………………………………………………………………………….9Aims and Objective …………………………………………………………………………………………………………….10Research Questions…………………………………………………………………………………………………………….11Organization of Chapters…………………………………………………………………………………………………….12Chapter 2LITERATURE REVIEWIntroduction……………………………………………………………………………………………………………………….13Definition of Integration…………………………………………………………………………………………………… 13The Concept and Factors of Social Integration ………………………………………………………………… 18Migration and Women……………………………………………………………………………………………………….23Social Integration of Migrant Women………………………………………………………………………………..27Chapter 3THEORETICAL FRAMEWORKFeminist Theory and Migration……………………………………………………………………………………………31Feminist Approach to Social Integration of Women Migrants……………………………………………..38Chapter 4METHODOLOGYQualitative Research Approach………………………………………………………………………………………….42Selection Process……………………………………………………………………………………………………………….45Data Collection…………………………………………………………………………………………………………………..47Ethical Considerations……………………………………………………………………………………………………………Chapter 5SOCIAL INTEGRATION OF AFGHAN WOMEN IN ISTANBULIntroduction………………………………………………………………………………………………………………………49A Historical Analysis of Afghan Women……………………………………………………………………………50History of Migration in Turkey…………………………………………………………………………………………. 56Integration Policy of Turkey………………………………………………………………………………………………60Social Integration of Afghan Women in Istanbul……………………………………………………………….68Chapter 6ANALYSIS OF DATAGeneral Characteristics of Interviewees………………………………………………………………………………78Factors of Social integration…………………………….………………………………………………………………...80Life before Migration…………………………………………………………………………………………………………..83Why Living in Zeytinburnu.......................................................................................................86Employment as …………………………………………………………………………………………………………………..88Language as a Tool for Social Integration…………………………………………………………………………….95The Impacts of Education on Social Integration…………………………………………………………………100Access to Health Services………………………………………………………………………………………………….103Socialization of Afghan Women…………………………………………………………………………………………108Experiences……………………………………………………………………………………………………………………….111Feelings of Belonging…………………………………………………………………………………………………………113The level of Respect…………………………………………………………………………………………………………1159Role Changes……………………………………………………………………………………………………………………118Expectations from the Turkish Government…………………………………………………………………….119Discussion of the Findings………………………………………………………………………………………………...121Chapter 7CONCLUSIONConclusion………………………………………………………………………………………………………………………126BIBLIOGRAPHY …………………………………………………………………………………………………………………131APPENDICESA. Questions………..……………………………………………………………………………………………………137B. References……………………………………………………………………………………………………………153
Keywords: Afgan Göçmenler; Afghan Migrants; Göçmenler, Afgan; Immigrants, Afghan; International relations; Kadın Göçmenler; Social Integration; Toplumsal Entegrasyon; Türkiye Women Migrants; Uluslararası ilişkiler